Combined effect of chitosan and gamma ray on quality of chilled fresh pork - WANG Jingjing; XU Chao; YANG Tilong; LIU Xunyue; DING Xingcheng (浙江大学学报. 农业与生命科学版)
Chilled pork is an important food in China due to its high nutritional value and excellent taste. However, the major problem associated with chilled pork is its susceptibility to contamination by pathogenic bacteria in the process of slaughtering, processing and transportation. Chitosan has been found to be a biocompatible, nonantigenic, biodegradable, nontoxic and biofunctional natural compound. And it was reported to have strong antimicrobial and antifungal activities, against a range of foodborne filamentous fungi, yeast, and bacteria. So chitosan makes it a potential natural source of food preservative or coating material. Food irradiation technology, as a kind of cold sterilization technology, has advantages of no residue, excellent sterilization effect and so on. Nowadays gamma irradiation is one of the most commonly used irradiation methods in China, due to its strong penetrating power, perfect technique and equipment protection, and excellent sterilization effect.Till now, the single effect of chitosan and gamma irradiation on chilled pork has been reported, but the combined effect of both chitosan and gamma ray on quality of chilled fresh pork has not been documented. This study was to explore a new way on shelf-life extension of chilled pork.Chilled fresh pork was soaked in 0%,1% and 1.5% chitosan solution, was vacuum-packed in polythene bags individually and then was subjected to 0,3,5 and 7 kGy doses of irradiation using 60Co gamma ray. Water content, pH value, chromaticity, lipid oxidation index of thiobarbituric acid (TBA) value, and total viable counts were measured at regular time. Plate count method was used to measure samples for the total number of colonies. Significance between treatments was determined by multi-factor analysis of variance (MANOVA) using SPSS 16.0.Results indicated that in the storage period, the range of water content was 69.88%-75.22% on the whole, and the pH value finally had a certain degree of rise, but the chitosan solution and irradiation treatment played a role in controlling pH rise. In terms of total viable counts, with the increase of irradiation dose and concentration of chitosan solution, the total colony number of samples declined. Chitosan combined with gamma ray treatment groups performed better in controlling the total number of colonies than the single application of gamma ray irradiation treatment groups and chitosan solution treatment groups. The TBA value of groups treated by chitosan solution at low doses was lower than the groups without chitosan solution treatment. In terms of color evaluation, at the first day after irradiation, a* value of the irradiation treatment groups was higher than that of treatment groups without irradiation, but b* value was the opposite. The a* value of all treatment groups increased with the irradiation dose at the first day, while the b* value of all treatment groups increased with the extension of storage time.In conclusion, compared with the single application of gamma irradiation treatment groups and chitosan solution treatment groups, though the chitosan-gamma ray combined skill has not shown obvious advantages in controlling water content and preventing color change and fat oxidation, it does better in controlling the rise of pH to some degree, and especially in controlling the total number of colonies, which is one of the most important factors influencing the shelf-life of food.